Skin substitutes based on allogenic fibroblasts or keratinocytes for chronic wounds not responding to conventional therapy: a retrospective observational study. Issue 1 (12th February 2014) - Pajardi, Giorgio; Rapisarda, Vicenzo; Somalvico, Francesco; Scotti, Andrea; Russo, Giulia Lo; Ciancio, Francesco; Sgrò, Arturo; Nebuloni, Manuela; Allevi, Raffaele; Torre, Maria L; Trabucchi, Emilio; Marazzi, Mario
Abstract: Chronic wounds are an expression of underlying complex pathologies and have a high incidence. Skin substitutes may represent an alternative approach to treat chronic ulcers. The aim of this retrospective observational study was to evaluate the wound reduction using skin substitutes based on allogenic fibroblasts or keratinocytes in 30 patients not responding to conventional therapy. Wound bed was prepared, then keratinocytes on Laserskin ® to treat superficial wounds or fibroblasts on Hyalograft 3D R to treat deep leg ulcers were applied, and finally wounds were treated with a secondary dressing composed of nanocrystalline silver. Once a week constructs were removed and new bioengineered products were applied, as well as nanocrystalline silver medication. In none of the cases under examination did any complications arise relating to the treatment. We also achieved a reduction in wound dimension and exudates, and an increase in wound bed score. Postoperative assessment shows a degree of healing that is statistically higher in the group treated with keratinocytes as compared with the fibroblast group. This retrospective study improves our understanding and defines the clinical indications for the various uses of the two types of skin substitutes.